Efficient DNA isolation from moroccan arar tree [Tetraclinis articulata (Vahl) Masters] leaves and optimization of the rapd-pcr molecular technique - Bakkali Yakhlefb, Salaheddine; Guenoun, Imane; kerdouh, Benaîssa; Hamamouch, Noureddine; Abourouh, Mohamed (Universidad de Málaga. Servicio de Publicaciones, 2010)
Efficient DNA isolation from Moroccan Arar tree [Tetraclinis articulata (Vahl) Masters] leaves and optimization of the RAPD-PCR molecular technique. Molecular genetic analysis of Arar tree [Tetraclinis articulata (Vahl) Masters] is often limited by the availability of fresh tissue and an efficient and reliable protocol for high quality genomic DNA extraction. In this study, two DNA extraction protocols were specifically developed for extracting high quality genomic DNA from Arar tree leaves: modified QIAgen DNA Kit and protocol developed by Ouenzar et al. (1998). DNA yield and purity were monitored by gel electrophoresis and by determining absorbance at UV (A260/A280 and A260/A230). Both ratios were between 1.7 and 2.0, indicating that the presence of contaminating metabolites was minimal. The DNA yield obtained ranged between 20 to 40 μg/g of plant materiel. The Ouenzar and collaborators protocol gave higher yield but was more time consuming compared to QIAgen Kit. However, both techniques gave DNA of good quality that is amenable to RAPD-PCR reactions. Additionally, restriction digestion and PCR analyses of the obtained DNA showed its compatibility with downstream applications. Randomly Amplified Polymorphic DNA profiling from the isolated DNA was optimized to produce scorable and clear amplicons. The presented protocols allow easy and high quality DNA isolation for genetic diversity studies within Arar tree.
Keywords: Hojas (Botánica) - Análisis; Botánica - Marruecos